MANAJEMEN STRATEGI OTORITAS JASA KEUANGAN (OJK) KALIMANTAN BARAT DALAM EDUKASI LITERASI KEUANGAN - Munawir Munawir; Maskupah Maskupah; Reza Kurniawan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
ABSTRACT From this research, it is seen that the level of financial literacy, especially for Indonesia, is still quite low, namely 32% compared to the literacy level of other countries such as Malaysia, Sri Lanka and Africa, the level of financial literacy in Indonesia is still lower.